The implementation of hadith studies for visually impaired people in Malaysia: issues and challenges - Ahmad, Norhafizah; Wan Zahari, Wan Ainaa Mardhiah; Kirin, Arwansyah (Penerbit UTHM, 2021)
Hadith is the second source in Islam after Quran. The role of hadith is very important in Islam especially in explaining and justifying the contents of Quran. The study of hadith for visually impaired people is very important and necessary in the special education system. There are some challenges that need to be considered in preserving the study of hadith for visually impaired people. These challenges must be faced together in order to create an equality of hadith educational opportunities toward visually impaired people regardless of their shortcomings. However, the exposures of hadith study occur only on a small scale while hadith also plays an important role in Muslim daily life. Therefore, the main objective of this article is to explain the issues and challenges faced by visually impaired people in implementing hadith studies. The qualitative approach is used in this research by using document analysis method from books, articles, journals, internet etc. The early finding shows that the hadith study for visually impaired people in Malaysia facing great issues and challenges. These challenges exist in several aspects including the lack of instructional resources, the weakness of educational institutions and the lack of teaching aid. Hence, this research is able to identify the issues and challenges faced by visually impaired people to pursuit hadith and guiding them to learn and love the Prophet SAW and his Sunnah.